Pelatihan pembuatan pupuk organik limbah ruminansia di Desa Selogabus Kecamatan Parengan Kabupaten Tuban: Training for production of ruminant waste organic fertilizer in Selogabus Village Parengan District, Tuban Regency - Siti Eliana Rochmi; Miyayu Soneta Sofyan; Gandul Atik Yuliani (IGKOJEI: Jurnal Pengabdian Masyarakat, 2023)
Tuban Regency applies a concept of an efficient livestock business considering that there are many potentials and opportunities that have not been utilized and managed optimally. Parengan Subdistrict is one of the areas in Tuban Regency with high potential for beef cattle and goats. The increase in the price of chemical fertilizers followed by restrictions on subsidized fertilizer quotas is the main problem of these communities. The potential raw materials that can be used to make organic fertilizers are available quite a lot in the area. The implementation of the PKM Community Service is carried out by approaching methods to solve partner problems. Community empowerment, especially breeders, is directed at activities to increase competitiveness and community participation through increasing the capacity and institutionalization of farmer human resources with various socialization counseling and training on making organic fertilizer for ruminant waste as a substitute for chemical fertilizers. The results achieved are in the form of improving the skills and knowledge of partners to process ruminant waste into organic fertilizer. Key words: Cow; Goat; Manure; Organic; Ruminant